Determination of The Most Suitable Milking Machine with Macbeth and Gray Relational Analysis Methods - Adem Köse; Hakan Murat Arslan; İsmail Durak (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2023)
Milking machines are an important element of the livestock sector, which is one of the main activities of the countries. Milking machines have become a part of the life of livestock keepers. Such equipment can be considered as applications of mechanical engineering on the livestock sector. Especially livestock enterprises are going through a difficult process in supplying such machines with optimum features and maximum benefit. In terms of productivity, competitiveness and sustainability of livestock sector enterprises, decision-making processes should be scientific. With this perspective, in this study, the problem of determining the optimum milking machine was evaluated with Multi-Criteria Decision Making (MCDM) methods. In the study, six different milking machines were analyzed with two different MCDM methods according to eight criteria. In this frame, the criterion weights of the related decision problem were calculated by the MACBETH method. Moreover, MACBETH and Gray Relational Analysis (GIA) methods were used separately to determine the most suitable milking machine. Furthermore, rankings obtained+- by different methods were tested with Spearman Rank Correlation Analysis and the result was found to be highly positive. The results of the study were shared with the decision makers. Besides, academic, and sectoral suggestions were made for future studies on similar topics.